LEADERSHIP DYNAMICS IN THE ERA OF EDUCATIONAL TRANSFORMATION: INTEGRATING THE CONCEPT OF ADAPTABLE LEADERSHIP IN SUSTAINABLE EDUCATIONAL ADMINISTRATION - Sidderatul Akbar; Syatria Adymas Pranajaya; Nurkadarwati; Rezkiyah Hoesny; Inayatul Mutmainnah (International Journal of Teaching and Learning, 2024)
This paper explored the evolving landscape of educational administration in the context of contemporary transformations within the education sector. Focusing on leadership dynamics, the study delved into integrating the concept of adaptable leadership as a critical element for sustainable educational administration. The research examined the nuances of leadership paradigms through a comprehensive literature review, emphasizing the interconnected dimensions of transformational, transactional, and adaptable leadership. The findings underscored the imperative for educational leaders to possess a versatile skill set and a strategic mindset to navigate the multifaceted challenges posed by educational transformation. Adaptable leadership was positioned not only as a reactive response to challenges but as a proactive and transformative force, empowering leaders to drive positive change, foster resilience, and promote innovation within educational institutions. The paper offered insights into the practical implications of embracing adaptable leadership for sustainable educational administration.